Children overdue for immunisation: a question of coverage or reporting? An audit of the Australian Immunisation Register - Charlee Law; Rhydwyn McGuire; Mark J. Ferson; Su Reid; Colleen Gately; Jody Stephenson; Sue Campbell‐Lloyd; Salwa Gabriel; Tambri Housen; Vicky Sheppeard; Paul Corben; David N. Durrheim; et al. (Elsevier, 2019)
Abstract Objective: Vaccinations in Australia are reportable to the Australian Immunisation Register (AIR). Following major immunisation policy initiatives, the New South Wales (NSW) Public Health Network undertook an audit to estimate true immunisation coverage of NSW children at one year of age, and explore reasons associated with under‐reporting. Methods: Cross‐sectional survey examining AIR immunisation records of a stratified random sample of 491 NSW children aged 12≤15 months at 30 September 2017 who were >30 days overdue for immunisation. Survey data were analysed using population weights. Results: Estimated true coverage of fully vaccinated one‐year‐old children in NSW is 96.2% (CI:95.9‐96.4), 2.1% higher than AIR reported coverage of 94.1%. Of the children reported as overdue on AIR, 34.9% (CI:30.9‐38.9) were actually fully vaccinated. No significant association was found between under‐reporting and socioeconomic status, rurality or reported local coverage level. Data errors in AIR uploading (at provider level) and duplicate records contributed to incorrect AIR coverage recording. Conclusions: Despite incentives to record childhood vaccinations on AIR, under‐reporting continues to be an important contributor to underestimation of true coverage in NSW. Implications for public health: More reliable transmission of encounters to AIR at provider level and removal of duplicates would improve accuracy of reported coverage.